Determinants of Recurrent Post-Ureteroscopy Hematuria: The Interplay of Segmental Arterial Injury, Ureteral Stent Dwell Time, and Mdr Klebsiella Bacteriuria—a Prospective Cohort Study - Dr. Sumit M Chaudhari (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Flexible ureterorenoscopy (URS/RIRS) with laser lithotripsy is widely used for ureteric and renal calculi, but uncommon hemorrhagic complications—including subcapsular/perinephric hematoma and renal arterial injuries—can present with delayed, recurrent gross hematuria. Diabetes mellitus, prolonged or repeat instrumentation, infected urine, and the presence of ureteral stents may amplify risk and complicate recovery. Methods: We report a single-patient case study of a 35-year-old man (Type-A personality, chronic smoker) with type 2 diabetes mellitus on oral agents who presented with obstructing distal ureteric calculus and underwent attempted right-sided RIRS with retrograde pyelography and double-J (DJ) stenting. Clinical, laboratory, microbiological, and imaging data from index admission through three subsequent hematuria readmissions were abstracted from the record. Interventions included antibiotics directed by culture and international guidance for multidrug-resistant (MDR) Enterobacterales, image-guided percutaneous drainage, selective segmental coil embolization, and staged stent removal. Outcomes included hemodynamic stability, hemoglobin and creatinine trends, hematoma burden, and hematuria resolution. (Framework informed by prior reports of post-URS renal hematoma/pseudoaneurysm and stent-related symptoms. Results: CT urography (16/2/25) showed a right subacute subcapsular hematoma (≈65–70 mL) with mild perinephric stranding, plus a small distal ureteric calculus; DJ stents were in situ bilaterally. The patient experienced four episodes of gross hematuria after the index procedure (two after angiographic coiling). Repeated urine cultures grew Klebsiella pneumoniae with MDR/ESBL phenotype; ceftazidime-avibactam ± aztreonam followed by step-down therapy were used per susceptibility and contemporary guidance. [9–12] Hemoglobin fell from 17.1 g/dL (pre-procedure) to 13–14 g/dL during readmissions but stabilized without transfusion; creatinine remained ≤1.2 mg/dL. Ultrasound (27/2/25) demonstrated interval reduction of the hematoma ( 45 mL). Targeted coil embolization of two upper-segmental arterial branches sealed contrast extravasation; a small-bore pigtail catheter yielded scant dark fluid (10–15 mL over 48 h). Recurrent hematuria ultimately ceased only after bilateral stent removal and a gentle check-URS showing no residual stone. Conclusion: In this young patient with diabetes, persistent post-RIRS hematuria reflected the combined effects of a subcapsular hematoma with a small arterial rent and stent-associated urothelial irritation in the setting of MDR Klebsiella bacteriuria. A step-up strategy—culture-guided antibiotics, limited drainage, selective angioembolization, and timely stent removal—achieved durable resolution while preserving renal function. Clinicians should suspect vascular injury or organized hematoma when hematuria recurs despite appropriate antimicrobial therapy, and should consider stent removal once obstruction and bleeding are controlled.